Automatic Tomato Plant Watering System Using Fuzzy Logic Control with Telegram-Based Monitoring System - Purwiyanti, Sri; Murdika, Umi; Pratama, Pinkga Nata; Repelianto, Ageng Sadnowo (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
In tomato plants, one of the decisive factors is the soil humidity factor, where the optimal humidity for tomato plants is 80%. For this reason, the tomato planting process requires regular and measurable irrigation or watering. This research aims to create an automatic watering system for tomato plants with soil humidity and pH detection. In this system, Fuzzy logic is used as the control method and this system is also equipped with a monitoring system using the telegram application. In this system, the humidity sensor and soil pH sensor will provide information about soil conditions and forward the electrical signal to the NodeMcu ESP32 microprocessor, as the control center and signal processing. This input signal is then processed using Fuzzy logic control to decide whether the system will activate the relay on the water pump. If the humidity value is <60%, the pump will activate and sprinkle water until the humidity reaches 80%. The measurement results of soil humidity, soil ph, and pump relay conditions will be sent via Internet of Things technology so that they can be monitored remotely using the Telegram application. From the research results, it is found that the system can work as expected with an accuracy value of 100% with a delay time for sending data to Telegram of 14.1 seconds. Keywords: Fuzzy logic, Humidity, NodeMcu, Sensor, Soil pH.